Culture and the assumptions about appearance and reality: a scientometric look at a century of research - Carollo, Alessandro; Stanzione, Alfonso Maria; Fong, Seraphina; Gabrieli, Giulio; Lee, Albert; Esposito, Gianluca (Frontiers in Psychology, 2023)
Introduction People represent the world in terms of two constructs: how something appears on the surface (appearance) and what it is underneath that surface (reality). Both constructs are central to various bodies of literature. What has not been done, however, is a systematic look at this collection of literature for overarching themes. Motivated by this research gap, the present scientometric review aimed to identify the common themes that penetrate through a century of scholarly work on appearance and reality. In doing so, this review also sketched a scientometric outline of the international network, pinpointing where the work was carried out. Methods With CiteSpace software, we computed an optimized document co-citation analysis with a sample of 4,771 documents (1929–2022), resulting in a network of 1,785 nodes. Results and discussion We identified impactful publications, summarized major intellectual movements, and identified five thematic clusters (“Perception of Counseling Services”, “Appearance and Reality in Sociocultural Evolution,” “Cultural Heritage and Identity,” “Media and Culture,” and “Cultural Identity”), all with theoretical and pragmatic implications which we discuss. A deeper look at these clusters reveals new empirical questions and promising directions for future research.